THE VICTIM HANDLING MODEL OF HUMAN TRAFFICKING THROUGH ECONOMIC INDEPENDENCE - Henny Nuraeny; Tanti Kirana Utami (Faculty of Law, Universitas Jenderal Soedirman, 2016)
Trafficking in persons is a modern trading of human slavery. Trafficking in persons is also one of the worst forms of violation of human dignity that results in trauma to the victims. To that end, there should be a comprehensive treatment for victims.The problems that can be studied is whether a model that can be applied in the treatment of victims of trafficking in Cianjur and disseminating technical how models Handling of Victims of Trafficking in Persons (Trafficking) in Cianjur.This study uses normative juridical approach and specification of descriptive analysis. The results of this study are alternative models to handle victims of trafficking in Cianjur is a service model based on inter-institutional and economic empowerment through planting camelina sativa with socialization techniques involving local government, private sector, community leaders and students through legal counseling and advocacy. Keywords: human trafficking, the victim handling model, socialization